ANALISIS DAN PENGEMBANGAN SISTEM INFORMASI MONITORING PENJUALAN OUTLET PADA UMKM MELUR LARIS - Pane, Eddis Syahputra; Afriansyah, Afriansyah (ZONAsi: Jurnal Sistem Informasi, 2024)
Sales require supervision or monitoring to determine the success achieved. UMKM Melur Laris specializes in selling chicken porridge which currently has more than 22 outlets where the management/owner must monitor or supervise sales developments in order to evaluate the level of sales at all outlets. The sales transaction input process currently carried out is by recording it in a sales report book, then the book is photographed and sent to the WhatsApp group. Every day the leadership recaps the results of sales, expenses, goods brought and leftover goods every day where there are many discrepancies with the results obtained, there is often repetition of data so that the accuracy of the calculations from the sales monitoring results is less accurate. So it is necessary to create an integrated system to help leaders control sales reports at all outlets in real time. As a result of this monitoring, leaders can evaluate sales at each outlet. This research will develop a sales monitoring system by integrating the information system of each outlet. The results of designing an Android-based sales monitoring information system application by integrating the sales system at outlets so that leaders can monitor the sales transaction process, transaction reports and stock reports at all outlets. The output of this research is OutletKu for monitoring application for the Melur Laris UMKM outlet, a HAKI (Intellectual Property Rights) certificate and a scientific journal published in the accredited national journal SINTA 4, a teaching material module that can be applied to web programming courses.